257 Reduction in EMS response times for out-of-hospital cardiac arrest using drone-like flying ambulances in large urban areas in France and Canada: An international, quasi-experimental study. (1st May 2022) - Heidet, M; Leung, KHB; Grunau, B; Chan, TCY; Deakin, J; Bougoin, W; Hubert, H; Jost, D; Frattini, B; Mermet, E; Vaux, J; Christenson, J; et al.
Abstract : Background: Shortening EMS response times lead to better outcomes after out-of-hospital cardiac arrest (OHCA). To overcome constraints encountered by ground ambulances, vertical take-off and landing (VTOL) capable flying ambulances are currently being developed. We compared simulated VTOL response to historical ground ambulance response for OHCAs in two large metropolitan areas in Europe and North America. Method: We conducted an international, multicenter, quasi-experimental study on adult, non-traumatic, EMS-assessed, non-EMS witnessed OHCA occurring in the greater Paris (France) and Vancouver (Canada) metropolitan areas, over a 2-year span (2018–2020). Data were drawn from Utstein-style, population-based OHCA registries. VTOL response times were simulated based on prototype specifications. Response times were defined from call reception to arrival at scene. Simulation models considered 1–5 VTOL vehicles placed in optimized locations. We determined the proportion of OHCAs for which VTOL response times were at least 1-min shorter than historical response from ground-based units. Results: In total, 13, 933 cases were included (6, 616 in Paris; 7, 317 in Vancouver). Simulated VTOL response times were substantially shorter than those of ground-based units, varying from 59% (1 VTOL) to 76% (5 VTOL) in Paris, and 17% (1 VTOL) to 40% (5 VTOL) in Vancouver. In both locations, median response times were reduced by 1–3 minutes, and 90th percentile response times by 1–5 minutes, varying upon model configuration. For OHCAs with improved response, the median improvement was 3–4 minutes, and 90th percentile improvement was 8–10 minutes in both areas. Conclusion: Simulation models of VTOL-capable flying ambulances show major theoretical reduction in EMS response times for OHCAs in two large European and North American metropolitan areas. Conflict of interest: None. Funding: None.